The Role of Sports Psychology in Enhancing Motivation and Performance of Beginner Basketball Athletes: A Sports Science Approach - I Putu Agus Dharma Hita (Yayasan Adra Karima Hubbi, 2024)
This research aims to explore the role of sports psychology in enhancing the motivation and performance of novice basketball athletes. Utilizing a literature review method, we investigated literature related to intrinsic motivation, self-confidence, psychological techniques, and social support in the context of sports. The results of the analysis indicate that intrinsic motivation, self-confidence, and social support play crucial roles in shaping the mental state and performance of athletes. Psychological techniques, such as visualization and relaxation, have also been proven effective in enhancing athlete performance. The practical implication of this research is the necessity of integrating sports psychology methods into training programs for novice basketball athletes to enhance their motivation and performance on the field